1996
DOI: 10.1002/j.1460-2075.1996.tb00691.x
|View full text |Cite
|
Sign up to set email alerts
|

The solution structure of the bovine leukaemia virus matrix protein and similarity with lentiviral matrix proteins.

Abstract: In the mature virion, retroviral matrix proteins are found in association with the inner face of the viral membrane. They play a critical role in determining the morphogenesis of virus assembly. We have determined the three‐dimensional solution structure of the bovine leukaemia virus (BLV) matrix protein by heteronuclear nuclear magnetic resonance. The protein contains four principal helices that are joined by short, partially structured loops. Despite no sequence similarity with the lentiviruses, the structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
36
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 35 publications
0
36
0
Order By: Relevance
“…On the other hand, we do find it compelling that there is remarkable similarity in the three-dimensional structures of all retroviral MA proteins, each having four major alpha helices separated by flexible loops, with the first two helices overlapping the second two (14,28,38,39). The structures of these evolutionarily diverse MA proteins are conserved even though the mechanisms that they use for membrane binding are not (e.g., the requirements for myristate and the clustering of basic residues differ for RSV and HIV) (55,63).…”
Section: Discussionmentioning
confidence: 72%
“…On the other hand, we do find it compelling that there is remarkable similarity in the three-dimensional structures of all retroviral MA proteins, each having four major alpha helices separated by flexible loops, with the first two helices overlapping the second two (14,28,38,39). The structures of these evolutionarily diverse MA proteins are conserved even though the mechanisms that they use for membrane binding are not (e.g., the requirements for myristate and the clustering of basic residues differ for RSV and HIV) (55,63).…”
Section: Discussionmentioning
confidence: 72%
“…It may be relevant in this regard that FIV has the shortest Env CT among the lentiviruses (4,41). By contrast, when considering retroviruses outside the lentiviruses, none of the MA structures available for human T-cell leukemia virus (HTLV) II (42), bovine leukemia virus (BLV) (43), Moloney murine leukemia virus (Mo-MLV) (38), Rous sarcoma virus (RSV) (44), or M-PMV (45) revealed an MA trimer, although, in every case except RSV, the authors felt that a trimeric MA was possible, based primarily on their close structural conservation with HIV-1 and SIV MA. It has been suggested that the formation of MA trimers is a precursor to Gag assembly in BLV and M-PMV (43, 45); however, our data suggest that in the case of HIV-1, loss of MA trimerization does not significantly impact viruslike particle assembly and therefore does not play a major role in Gag lattice formation.…”
Section: Discussionmentioning
confidence: 99%
“…Similar residues in the HIV-1 NC zinc finger have been implicated in interactions with SL3 RNA and have been shown to be important for RNA packaging by mutagenesis studies (9). The basic residues in the BLV MA that caused the greatest defects in RNA packaging (i.e., K41 and H45) are located in ␣-helix B (28). Presently, no structural data are available regarding the potential viral RNA-MA protein interactions.…”
Section: Discussionmentioning
confidence: 99%